ASPEK HUKUM TERHADAP PENYALURAN KREDIT MIKRO YANG BERMASALAH PADA PT. BANK MANDIRI (PERSERO) TBK CABANG SAMARINDA - Greschela, Greschela (Journal of Law ( Jurnal Ilmu Hukum ), 2018)
ABSTRACT                Problem loans often occur in credit agreements. In micro credit channeling by PT. Bank Mandiri (Persero) Tbk Samarinda Branch, not always the credit provided by Bank Mandiri to the debtor will run smoothly as expected in the credit agreement. Environmental conditions, moral factors and weaknesses that can affect the smooth debtor's obligations with Bank Mandiri so that loans channeled to debtors have the potential to cause failure or problems. For that effort made by Bank Mandiri in the settlement of problematic microcredit through the settlement of billing, Restructuring, Settlement, Collateral Liquidation, Settlement via third party, NPL (Non Performing Loan) Disposal, Delete Book and Clear Billing. The purpose of the research is to understand and know the factors that cause the problem of microcredit problems and efforts to solve them. The method used in this paper is an empirical juridical method that focuses on field research, which examines the applicable legal provisions as well as actual or actual circumstances. Keywords : Credit Micro, The Credit Agreement, Bad Debts and completion.